A educação ambiental nos movimentos juvenis : diálogos com líderes de sete grupos em Mato Grosso - Silva, Fernanda Domingos da (2013)
This present study aims to investigate if different youth movements from Mato Grosso conduct and perform environmental education actions. Environmental education must consider the relationships between human beings, society and nature, and to conduct the research we used as inspiration its phenomenological triad, composed by the dimensions “I - Other – World”. In the dimension “I”, we investigate the identities of the people interviewed and their perceptions about what is to be young, in the dimension “Other”, we glimpse at perceptions and actions about politics, and, in the dimension “World”, we seek to understand the perceptions of these people and their movements, related to Environment (E) and Environmental Education (EE), as well as the actions that may exist. To materialize the survey, between October 2011 and June 2012, we interviewed leaders from seven youth movements, linked to different themes: Favela Ativa, UBES, CJ Juína, GRADELOS, Youth from PT, FETAGRI and PJ from Alta Floresta. As methodology, we used the study of collective case, which enables to study different cases in order to comprehend a subject or phenomenon. In relation to the “I” dimension, it was predominant among the people interviewed the comprehension of the youth as a state of spirit. This revealed that the strength of the molded images on youth, specially those associated to militancy was more important to the identification of these people than their delimitation to an age group, because their identities are constructed essentially in militancy. Indeed, we observed a profound relationship between their identities and those of their own group of acting. Besides, among these people was notorious the participation in more than one movement, simultaneously, and also the acting on more than one front inside the movement itself, or on different fronts outside the movement, but directly related to its cause. In this regard, we consider that the consistency in their identities comes from the comprehension that the cause for which they act can manifest itself in different ways, which makes it possible to act in more than one movement, since such action is in connection with their primary identities. Regarding to the scale “Other”, all the leaders considered that the actions of their groups are related to politics, having been prevalent the perception of politics as a form of dialogue and collective construction of something. In the “World” dimension, people interviewed showed varied perceptions about E and EE. According to their leaders, in relation to the E, would be five the groups acting (Favela Ativa, CJ, FETAGRI, PJ, UBES), and in relation to the EE, would be four groups (Favela Ativa, CJ, FETAGRI, PJ). However, only the CJ and FETAGRI worked the environmental theme truly integrated to their actions. We believe that the reasons that lead these groups to perform, not perform, or not perform effectively EE issues and actions, are due to an intertwining of perceptions and identities of these movements, which influence the way they act about reality. The involvement of different youth movements with the environment theme, and with EE, can be enhanced by EE mainstreaming in schools, and its interconnection with groups that may contribute to its environmentalization.